Role of low density lipoprotein - cholesterol in focal adhesion assembly and migration of cancer cells - Engel, Johanna; Justus Liebig University Giessen (My University, 2024)
In cells lacking the Niemann-Pick type C1 (NPC1) cholesterol transporter, cholesterol accumulation in late endosomes (LE) and an inability to distribute cholesterol from LE to other cell compartments causes impaired cell migration. It was speculated that cholesterol released from LE in NPC1 mutant Chinese hamster ovary (CHO) cells by annexin A6 (AnxA6) depletion could be delivered to the cell surface and support the focal adhesion (FA) dynamics required for migration. Cells obtain cholesterol through low-density lipoprotein (LDL) uptake, which is then delivered to LE and distributed to other sites. To study regulatory circuits that link LDL-cholesterol trafficking with the migratory machinery in CHO wild type (WT), NPC1 mutant CHO M12 and AnxA6-depleted CHO M12 cells (M12-A6ko), the relative expression levels of proteins involved in cholesterol homeostasis were compared. Furthermore, the number, location, and size of FA were analysed and the distribution and colocalisation of FA components assessed by immunofluorescence microscopy. Western blot analysis revealed that cholesterol sequestration in CHO M12 appears to affect the activation status of key migration signalling proteins. Phosphorylation of focal adhesion kinase (Y861 FAK), Src (Y416 Src) and p130Cas was greatly reduced in CHO M12 and M12-A6ko at steady state. It was speculated that this coincides with improper translocation of Src kinase and FAK to the cell surface to regulate FA (dis)assembly. Underlying mechanisms likely include the dysregulation of cholesterol-sensitive SNARE proteins, which regulate exocytic transport of membrane and FA proteins to the cell surface. Microscope-based quantification of the distribution of activated FAK (pY397 FAK, pY861 FAK), vinculin and paxillin in NPC1 mutants revealed an increased number and size of FA in the cell body, while the typical peripheral FA distribution observed in WT cells was absent. Interestingly, ectopic expression of constitutively active Y527F Src but not WT Src, appeared to restore FA distribution in NPC1 mutants, indicating that oncogenic Src can overcome dysregulated cholesterol distribution in these cells to coordinate FA dynamics. Strikingly, normalisation of cholesterol homeostasis in M12-A6ko cells correlated with restoration of cholesterol transport to the cell edge, as measured by the increased colocalisation of the cholesterol biosensor D4H with pY861 FAK and vinculin. Hence, AnxA6-regulated transport routes seem to contribute to cholesterol delivery to FA structures, thereby improving NPC1 mutant cell migratory behaviour.
Keywords: Annexin A6; focal adhesion; LDL-cholesterol; cell migration; ddc:570; ddc:610